THE INFLUENCE OF ACTIVE AND REACTIVE POWER IN THE ELECTRICAL NETWORK ON THE ELECTRICAL SYSTEM - B.B. Abdurahimov (American Journals, 2023)
This article reflects on the problems encountered in the processes by the author today over the negative and positive consequences caused by the impact of active and reactive power on the electrical system in the electrical network.
Keywords: Synusoidal voltage, frequency, power grid, active and reavant power, vine.